Extra Corporeal Membrane Oxygenation in the Treatment of Human Immunodeficiency Virus-Related P. jirovecii Pneumonia - Sara Lacerda Pereira; Elsa Branco; Ana Sofia Faustino; Paulo Figueiredo; António Sarmento; Lurdes Santos (MDPI AG, 2021)
Despite the undeniable complexity one may encounter while managing critically ill patients with human immunodeficiency virus infection (HIV), intensive care unit-related mortality has declined in recent years, not only because of more efficacious antiretroviral therapy (ART) but also due to the advances in critical support. However, the use of extracorporeal membrane oxygenation (ECMO) in these patients remains controversial. We report four cases of HIV-infected patients with Pneumocystis jirovecii pneumonia (PJP) and acute respiratory distress syndrome (ARDS) treated with ECMO support and discuss its indications and possible role in the prevention of barotrauma and ventilator- induced lung injury (VILI). The eventually favorable clinical course of the patients that we present suggests that although immune status is an important aspect in the decision to initiate ECMO support, this technology can provide real benefit in some patients with severe HIV-related refractory ARDS.